Emissions trading in Australia : developing a framework - Hinchy, Michael; Fisher, Brian S. (Brian Stanley); Graham, Brett; Australian Bureau of Agricultural and Resource Economics (Canberra [A.C.T.] : ABARE, 1998)
The purpose of this report is to contribute to the climate change policy debate by providing a discussion of the issues that need to be considered in establishing a framework for greenhouse gas emissions trading. In setting up a domestic trading scheme it seems desirable to bear in mind the likely necessity of integrating with an international scheme in the future.
Summary -- 1. Introduction -- 2. Static design issues -- 3. Sink enhancement and diminution -- 4. Dynamic design issues -- 5. Integration with an international scheme -- Appendix -- Boxes -- References.
"ABARE project 1535" --verso T.p.
Includes bibliographical references, p. 60-62.
Keywords: Greenhouse gases -- Environmental aspects -- Australia; Climatic changes -- Australia; Energy consumption -- Australia